Effect of Porcine Clostridium perfringens on Intestinal Barrier, Immunity, and Quantitative Analysis of Intestinal Bacterial Communities in Mice - Jiang, Zipeng; Su, Weifa; Wen, Chaoyue; Li, Wentao; Zhang, Yu; Gong, Tao; Du, Shuai; Wang, Xinxia; Lu, Zeqing; Jin, Mingliang; Wang, Yizhen (Frontiers in Veterinary Science, 2022)
Clostridium perfringens is one of the main pathogens which can cause a range of histotoxic and enteric diseases in humans or animals. C. perfringens can induce ‘sudden disease’ and hemorrhagic necrotizing in pigs. This study aimed to isolate the porcine C. perfringens that caused the death of pig and build a model of mice infected porcine C. perfringens. We detected the effects of C. perfringens on the growth performance, immune status, intestinal barrier integrity, apoptosis and gut microbiota of mice. In general, total 32 six-week-old male C57BL/6 mice were randomly divided into four groups, eight mice in each group. Control group was orally dosed with PBS (200 μL) on day 0. Low group, Medium group, and High group were pretreated with resuspension porcine C. perfringens 8.0 × 107 CFU/mL, 4.0 × 108 CFU/mL and 2.0 × 109 CFU/mL on day 0, respectively. The results showed that the growth performance of mice declined and intestinal structure was serious damaged in High group. Meanwhile, the pro-inflammatory factors (IL-1β, TNF-α, IL-6) were significantly increased (P < 0.05) in High group than other groups. Similarly, the tight junctions and apoptosis related genes expression also reflected that High dose caused a negative effect on the intestinal barrier and cell reaction in the jejunum of mice. Besides, the enumerations of pathogens and probiotics illustrated that the High group treatment significantly increased (P < 0.05) the population of C. perfringens and Escherichia coli, and dramatically decreased (P < 0.05) the population of Lactobacillus. In general, High group may meet the requirements in construct a C. perfringens infected mouse model and have the stronger infection ability than 8.0 × 107 CFU/mL, 4.0 × 108 CFU/mL of C. perfringens. These results provided an experimental and theoretical basis for the construction of porcine C. perfringens infection model in mice.